Nucleosome assembly protein 1 is a regulator of histone H1 acetylation. (22nd September 2021) - Yoneda, Mitsuhiro; Yasui, Kiyoshi; Nakagawa, Takeya; Hattori, Naoko; Ito, Takashi
Abstract: Acetylation of histone H1 is generally considered to activate transcription, whereas deacetylation of H1 represses transcription. However, the precise mechanism of the acetylation is unknown. Here, using chromatography, we identified nucleosome assembly protein 1 (NAP-1) as having inhibitory activity against histone H1 acetylation by acetyltransferase p300. We found that native NAP-1 interacts with H1 in a Drosophila crude extract. We also found that it inhibits the deacetylation of histone H1 by histone deacetylase 1. The core histones in nucleosomes were acetylated in a GAL4–VP16 transcriptional activator-dependent manner in vitro . This acetylation was strongly repressed by hypoacetylated H1 but to a lesser extent by hyperacetylated H1. Consistent with these findings, a micrococcal nuclease assay indicated that hypoacetylated H1, which represses activator-dependent acetylation, was incorporated into chromatin, whereas hyperacetylated H1 was not. To determine the contribution of NAP-1 to transcriptional regulation in vivo, we compared NAP-1 knockdown (KD) with coactivator CREB-binding protein (CBP) KD using RNA sequencing in Drosophila Schneider 2 cells. Most genes were downregulated rather than upregulated by NAP-1 KD, and those downregulated genes were also downregulated by CBP KD. Our results suggest that NAP-1 plays a role in transcriptional regulation by fine-tuning the acetylation of histone H1. Graphical Abstract